1427. Key Clinical Research Questions Asked During Epidemic Respiratory Outbreaks: A Systematic Review of the Literature Published on Severe Acute Respiratory Syndrome and Middle East Respiratory Syndrome. (31st December 2020) - Harris, Carlyn L; Carson, Gail; Nair, Harish
Abstract: Background: As evidenced by the COVID-19 pandemic, rapid collection of data on clinical characterization, treatment, and diagnostics to inform rapid public health response is paramount in an outbreak of a novel infectious agent. In 2018, The World Health Organization R&D Blueprint identified a list of priority diseases for accelerated research based on their potential to cause a public health emergency. Among these diseases were Severe acute respiratory syndrome-coronavirus (SARS-CoV) and Middle East respiratory syndrome-coronavirus (MERS-CoV). To facilitate a rapid research response during an outbreak, standardized research protocols must be prepared before the outbreak occurs. The aim of this systematic review is to identify the most common clinical research questions asked during outbreaks of SARS-CoV and MERS-CoV to inform future clinical research protocol development for coronaviruses. Methods: Medline, Embase, and Global Health bibliographic databases were searched to identify clinical studies published on SARS-CoV and MERS-CoV in the outbreak setting. Studies were grouped thematically according to the clinical research question addressed. Results: From the research questions and objectives, eleven themes in the literature were identified: Clinical characterisation, prognosis, diagnosis, clinical management, viral pathogenesis, epidemiological characterisation, infection prevention and control, transmission, susceptibility, psychosocial, and aetiology. Case series made up the highest proportion of study designs, while clinical trials made up the lowest. 83% of the SARS-CoV studies were published after the end of the outbreak. Themes and key clinical questions asked during outbreaks of SARS and MERS Conclusion: The thematic analysis was used to identify the key clinical research questions asked during outbreaks of SARS-CoV and MERS-CoV and study designs were recommended to answer these questions. By defining the key clinical research questions, this study provides a first step in creating standardized clinical research protocols and defining core data variables to be collected during future outbreaks of respiratory coronaviruses. Disclosures: All Authors : No reported disclosures